ANALISIS BAURAN PRODUK DAN LOYALITAS NASABAH STUDI KASUS PADA BANK NAGARI CABANG SOLOK - Fazril, Fazril (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2008)
This research has background by condition of loyalitas clien Bank Nagari Solok. Hypotesis from this research is how product mix and loyalitas clien Bank Nagari Solok. This research has sample about 370 people and use the accident sampling. The technique analysis of data is analysis descriptive. The result this research are: in general the client have hight loyalitas of Bank Nagari at Solok. It can see with clien scor rate about 4,15 with level 83,03 percent. According indicator in the hight scor variable of loyalitas clien can do with Bank functional for all transaction who to do by clien Bank Nagari at Solok. The interesting product mix that give contribution and influence for clien loyalitas Bank Nagari at Solok is easy in proces opening of new account who to do by clien Bank Nagari at Solok.